(untitled) (Revista de Crítica Literaria Latinoamericana, 2018)
In our interpretation of Noli me tangere, by José Rizal, the baroque public celebrations are considered an essential element that prevents the Philippine people from getting free from the traditional canonical and circular religious timeline to enter the lineal one of modern times that leads to progress. This paper proposes a literary analysis of the narrative structure of this novel based on the identification of the festive celebrations associated with colonial power and the church (urban setting), as opposed to those connected to secular feasts (marginal locations or nature) which the rebellious characters (representing Romanticism and Enlightment) celebrate as a way to freedom.